Mapping of Dolphin Watching Accommodation and Tourist Facilities in the Lovina Coastal Area: A Study in Temukus, Kaliasem and Kalibukbuk Villages - Ni Ketut Catur Wulandari; Ni Nyoman Tri Wulandari; Leli Kasrian Br Gultom; I Made Angga Santika Sangging; I Putu Ananda Citra; Made Dwipayana (Jurnal Ilmiah Ilmu Sosial, 2026)
Lovina Beach in Buleleng Regency, Bali, is a well-known marine tourism destination whose main attraction is dolphin watching. However, disparities in the distribution of tourism facilities, lack of service standardization, and absence of cross-village coordination remain major challenges that threaten service quality and environmental sustainability. Previous studies have highlighted ecological and management issues but have not focused on spatial mapping and facility distribution inequalities. This study aims to map the distribution of dolphin watching accommodations and tourist facilities in Temukus, Kaliasem, and Kalibukbuk Villages, as well as to analyze differences in ticket prices, boat capacity, and management challenges between villages. The research employed a descriptive qualitative method combined with GIS-based mapping, using data from field observations, in-depth interviews with tourism actors, and documentation between May–June 2025. Results show an uneven distribution of facilities, with Kalibukbuk having the most complete infrastructure while Temukus and Kaliasem remain underdeveloped. Ticket prices are uniform at IDR 100,000 despite service disparities, and jukung departure routes converge at the same observation point, increasing ecological risks. Institutional fragmentation and absence of integrated regulations exacerbate management inefficiencies. The study recommends establishing a cross-village coordination forum, implementing service-based tariff standards, applying zoning for departure points, enhancing local human resource capacity, and developing a location-based digital information system. These strategies are expected to promote equitable, sustainable, and environmentally responsible coastal tourism governance.